Correlation of SOFA Score and Hormone Value for Predicting 28-days Mortality for Septic Patients - Zulkifli; Agustina Br Haloho; Ziske Maritska; Dipta Anggara (Journal of Anesthesiology and Clinical Research, 2021)
Introduction. Sepsis is a group of symptoms of organ dysfunction that can be life-threatening because of dysregulation of body response toward ongoing infection. Organ dysfunction in sepsis can be measured by Sequential Organ Failure Assessment (SOFA) and T3 hormone. The study was aimed to identify the correlation of T3 in predicting mortality of 28 days patients in Intensive Care Unit RSMH Palembang. Method. This study design is cohort prospective. The inclusion criteria consist of a patient diagnosed with sepsis and septic shock in the Intensive Care Unit, 18-64 years old. Patients with a history of thyroid disease, pregnant or post-pregnancy, the patient admitted in referral from other hospitals, and patients with a history of psychiatry medication and thyroid medication were excluded. Data collected is the patient whose stay in Intensive Care Unit RSMH followed in 28 days from January 2021 until the sample was fulfilled (39 samples). Analyzing data was SPSS version 23 with chi-square analysis and Fisher's Exact to identify the relationship. Pearson correlation to identify correlation coefficient, and Medical application to measure AUC, cutoff value, sensitivity, and specificity. Result. The result showed that age (p=0,445). gender (p=1,00), need of ICU (p=0,228), isolation-nonisolation ward (p=0,437) didn't have any significant relationship toward mortality. SOFA score correlate statistically with positive correlation and medium strength (0,633) toward mortality of sepsis patient (p=0,000). T3 hormon correlate positively with medium strength (0,514) toward mortality of sepsis patient (p=0,001). T3 hormone toward SOFA correlate negatively (-0,365) with significant correlation (p=0,22). T3 hormone has AUC 0,291 with sensitivity 3,3% and specificity 67,7%. Conclusion. T3 hormone has a significant negative correlation to mortality in sepsis patients but cannot be used to predict mortality with a low AUC value (0,291).